Specific interactions of distamycin A and its analogs with (A-T) rich and (G-C) rich duplex regions of DNA and deoxypolynucleotides. - Luck, G (1977)
The specific interaction of distamycin A and analogs with DNA's and synthetic deoxypolynucleotide duplexes were studied in detail by means of circular dichroism and the data were analyzed together with viscosity results of several natural DNA's. At low ligand to nucleotide ratio the previously reported specific binding to (A-T) pairs of DNA is verified by a highly favoured interaction with (A-T)-enriched segments of distamycins containing four and five methylpyrrole carboxamide units. At higher distamycin concentration a second specific binding to (G-C) pairs most probably through hydrogen bonding is established. Viscometric results suggest a distamycin-induced local bending of the helix and could support the idea of a preferential alignment of the ligand molecule along only one strand in the groove which differs from the netropsin interaction mechanism. The possibility of an overlapping binding of the oligopeptides in the small groove is discussed.